2008
DOI: 10.1111/j.1444-2906.2007.01498.x
|View full text |Cite
|
Sign up to set email alerts
|

Bioremediation of organically enriched sediment deposited below fish farms with artificially mass-cultured colonies of a deposit-feeding polychaete Capitella sp. I

Abstract: For bioremediation of organically enriched sediment deposited below fish farms, the extremely high potential for population growth of a deposit-feeding polychaete, Capitella sp. I, in the organically enriched sediment, and the effect on decomposition of organic matter in the sediment, were examined. A mass-culturing technique was conducted for this species. Bioremediation experiments were conducted on the organically enriched sediment in a fish farm in Kusuura Bay, Japan in 2003-2006. Approximately 1.7 million… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 28 publications
1
43
0
Order By: Relevance
“…I sensu Grassle and Grassle (1976) from Massachusetts (USA) based on the karyotype, ability to interbreed, and lifehistory; this taxon has subsequently been reported from Japan in various ecological papers under the name Capitella sp. I (e.g., Tsutsumi, 2005;Tsutsumi et al, 2005a, b;Kinoshita et al, 2008) or C. teleta (Nishi et al, 2010;Kanaya, 2014;Kanaya et al, 2015). These records, together with reports from California and the Mediterranean , suggested that C. teleta is broadly distributed ( Fig.…”
Section: Introductionmentioning
confidence: 86%
“…I sensu Grassle and Grassle (1976) from Massachusetts (USA) based on the karyotype, ability to interbreed, and lifehistory; this taxon has subsequently been reported from Japan in various ecological papers under the name Capitella sp. I (e.g., Tsutsumi, 2005;Tsutsumi et al, 2005a, b;Kinoshita et al, 2008) or C. teleta (Nishi et al, 2010;Kanaya, 2014;Kanaya et al, 2015). These records, together with reports from California and the Mediterranean , suggested that C. teleta is broadly distributed ( Fig.…”
Section: Introductionmentioning
confidence: 86%
“…I on the sea floor in early November in 2004(Tsutsumi et al, 2005aKinoshita et al, 2008). The Capitella colonies increased rapidly in the cold seasons, and reached a peak density in March 2005 (528 000 individuals per m 2 ) and January 2006 (1 028 000 individuals per m 2 ) (Figure 1a).…”
Section: Discussionmentioning
confidence: 99%
“…Kusuura Bay is an enclosed bay (11.4 km 2 area, 4 Â 3.5 km 2 ), located between Amakusa Kamishima and Amakusa Shimoshima Islands in Kyushu, (Tsutsumi et al, 2005a;Kinoshita et al, 2008).…”
Section: Study Areamentioning
confidence: 99%
See 2 more Smart Citations